Long-term exposure to air pollution and cognitive function in older adults: a systematic review and meta-analysis - McLachlan, Jack; Cox, Simon R.; Pearce, Jamie; Valdés Hernández, Maria del C. (Frontiers in Environmental Health, 2023)
Background: Now more than ever before, air pollution and cognitive decline are global concerns. Credible links are now emerging between exposure to specific pollutants and cognitive decline. However, the role of specific pollutants on different cognitive domains in adults are inconclusive as the pathways to cognitive decline remain poorly understood. Objective: To systematically review and meta-analyse the evidence for the association between long-term air pollution exposure and cognitive function in adults. Data sources: Web of Science, PubMed, Embase searched up to February 2021 with no language restrictions. Individual studies were identified from similar review articles. Eligibility criteria: Studies investigating the long-term (> 3 years) associations between airborne pollutants and cognitive function in older adults (> 50 years old). Results: From 1996 records, 26 satisfied the inclusion criteria. The total sample size included over 2.4 million (53.8% female) subjects with ages ranging from 45 to 100 years (estimated mean age 70 years). Only 18/26 publications included both male and female subjects. Pollutants reported included particulate matter ≤ 2.5 µm (PM2.5); particulate matter ≤10 µm (PM10); nitrogen dioxide (NO2); nitrogen oxide species (NOx) and ozone (O3). Papers showed great variance in their study characteristics, air pollution modelling methodology and assessment of cognitive domain. Long-term exposure to increased levels of PM2.5 and NO2 were most strongly associated with increased risk of dementia. Decline in cognitive function, executive function, memory and language were most strongly associated with greater exposure to PM2.5, PM10 and NO2 to varying degrees. Conclusion: An increasing number of studies are supporting the hypothesis that greater exposure to air pollutants is associated with decline in cognitive functions.